ENdb: a manually curated database of experimentally supported enhancers for human and mouse. Issue Volume 48:Issue D1(2020) (29th October 2019) - Bai, Xuefeng; Shi, Shanshan; Ai, Bo; Jiang, Yong; Liu, Yuejuan; Han, Xiaole; Xu, Mingcong; Pan, Qi; Wang, Fan; Wang, Qiuyu; Zhang, Jian; Li, Xuecang; et al.
Abstract: Enhancers are a class of cis -regulatory elements that can increase gene transcription by forming loops in intergenic regions, introns and exons. Enhancers, as well as their associated target genes, and transcription factors (TFs) that bind to them, are highly associated with human disease and biological processes. Although some enhancer databases have been published, most only focus on enhancers identified by high-throughput experimental techniques. Therefore, it is highly desirable to construct a comprehensive resource of manually curated enhancers and their related information based on low-throughput experimental evidences. Here, we established a comprehensive manually-curated enhancer database for human and mouse, which provides a resource for experimentally supported enhancers, and to annotate the detailed information of enhancers. The current release of ENdb documents 737 experimentally validated enhancers and their related information, including 384 target genes, 263 TFs, 110 diseases and 153 functions in human and mouse. Moreover, the enhancer-related information was supported by experimental evidences, such as RNAi, in vitro knockdown, western blotting, qRT-PCR, luciferase reporter assay, chromatin conformation capture (3C) and chromosome conformation capture-on-chip (4C) assays. ENdb provides a user-friendly interface to query, browse and visualize the detailed information of enhancers. The database is available at http://www.licpathway.net/ENdb .